2017
DOI: 10.1039/c7cp02687k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into dioxygen activation, oxygen atom exchange and substrate epoxidation by AsqJ dioxygenase from quantum mechanical/molecular mechanical calculations

Abstract: Herein, we use in-protein quantum mechanical/molecular mechanical (QM/MM) calculations to elucidate the mechanism of dioxygen activation, oxygen atom exchange and substrate epoxidation processes by AsqJ, an Fe/α-ketoglutarate-dependent dioxygenase (α-KGD) using a 2-His-1-Asp facial triad. Our results demonstrated that the whole reaction proceeds through a quintet surface. The dioxygen activation by AsqJ leads to a quintet penta-coordinated Fe-oxo species, which has a square pyramidal geometry with the oxo grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 74 publications
12
71
1
Order By: Relevance
“…We found that the dioxygen molecule prefers to bind to the iron in a side‐on mode as suggested from the experiment . Most theoretical studies on the nonheme iron enzymes predicted a high spin septet ground state for the Fe−O 2 complex . Here too, the septet state with the side‐on conformation ( 7 1 side‐on in Figure A) was found to be the most stable one, and then was set as the reference point of 0 kcal mol −1 .…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…We found that the dioxygen molecule prefers to bind to the iron in a side‐on mode as suggested from the experiment . Most theoretical studies on the nonheme iron enzymes predicted a high spin septet ground state for the Fe−O 2 complex . Here too, the septet state with the side‐on conformation ( 7 1 side‐on in Figure A) was found to be the most stable one, and then was set as the reference point of 0 kcal mol −1 .…”
Section: Resultssupporting
confidence: 53%
“…[6] Most theoretical studies on the nonheme iron enzymes predicted a high spin septet ground state for the FeÀ O 2 complex. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Here too, the septet state with the side-on conformation ( 7 1 side-on in Figure 1A) was found to be the most stable one, and then was set as the reference point of 0 kcal mol À 1 . To better understand the electronic structure, analysis of the spin natural orbitals (SNOs) were also performed for the FeÀ O 2 complexes.…”
Section: Dioxygen Binding To the Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a complex is the most likely species to initiate the oxidation of the primary substrate, as the previous Mössbauer and QM/MM study on AsqJ has revealed [10]. ⁠…”
Section: Resultsmentioning
confidence: 96%
“…The process was investigated by QM/MM calculations and the proposed mechanism involves the formation of a bond between C10 and the oxo ligand of the oxoferryl species that yields a C3-centered radical [10]. Comparison of these results with the ones reported here for desaturation shows that both AsqJ-catalysed reactions are initiated at the C10 position.…”
Section: Resultsmentioning
confidence: 99%